Gender differences, facial profile and treatment need of malocclusion for a sample of Al-Muthanna governorate students aged 15 years - Hayder S Al-Atabi (College of Dentistry/ University of Baghdad, 2014)
Background: Survey of the occlusion in population groups usually include in their objections the academic assessment of occlusal feature, the planning resources for public health treatment programmers, the comparison of different population and the screening of groups for orthodontic treatment. Likewise a thorough investigation of the occurrence of malocclusions among schoolstudents would be of major importance in the planning of orthodontic treatment in the public dental health services. For this purpose it is necessary to have detailed information on the prevalence of individual malocclusion among boys and girls at different ages distributed regionally, and moreover, an analysis of the need for orthodontic treatment in the different school classes. Materials and methods: This study was conducted from 20th October 2011 to 9th May 2013 on (3424 ) students (1712 males and 1712 females); from which 62 students (1.8%) were excluded because of incomplete information (no molar relation can be attended) giving a valid sample of 3362 (1681 males and 1681 females) aged (15) years old were studied with respect to facial profile ,sagittal occlusion according to Angle's classification, overjet, overbite, anterior crossbite , posterior crossbite, scissorsbite, rotation and displacement spacing and crowding. Results: The normal profile were presented in (73.76%) students (74%) males and (73.53%) females. Convex profiles were presented (20.34%) students (20.46%) males and (20.23%) females. A concave profile were presented in (5.9%) students (5.54%) males and (6.24%) females), The malocclusion were presented (73.05%) students (73.46%) males and (72.64%) females, According to the Dental health component of index of the orthodontic treatment subjects with no need for treatment were about 44.11% , the subjects who need little treatment were about 26.82%, 13.06% of the subjects who need moderate treatment, 10.03% great treatment need and about 5.98% very greatly treatment need. Conclusions: Orthodontic treatment need according to IOTN shows that there was no significant difference between males and females in the malocclusion, Facial profile and treatment need.